2020
DOI: 10.1021/acsaem.0c02200
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reconstruction of Zn0.3Co2.7(PO4)2·4H2O for Enhanced Water Oxidation Performance

Abstract: Developing electrocatalysts with abundant active sites is a substantial challenge to reduce the overpotentials for the water splitting reaction. Toward the oxygen evolution reaction (OER) in alkaline medium, designing precatalysts that could provide abundant catalytic active centers can significantly improve the electrocatalytic activity. This work demonstrates the production of active α-Co(OH) 2 /CoOOH species using the sacrificial pre-catalyst Zn x /Co 3−x (PO 4 ) 2 •4H 2 O (ZCP) (x = 0.15−0.9), which was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
(101 reference statements)
1
19
0
Order By: Relevance
“…R CT values have an inverse relationship with power output because higher resistance to the charge transfer process inhibits the ow of charge carriers, lowering HV activity. 26,27 The resistance decreases up to 6 mg and then increases, indicating faster charge transfer kinetics at 6 mg for the 3 cm  1.5 cm size. With loading masses above 6 mg the lm loses its stability in water, conrming optimal lm formation at 6 mg for 3 cm  1.5 cm.…”
Section: Resultsmentioning
confidence: 98%
“…R CT values have an inverse relationship with power output because higher resistance to the charge transfer process inhibits the ow of charge carriers, lowering HV activity. 26,27 The resistance decreases up to 6 mg and then increases, indicating faster charge transfer kinetics at 6 mg for the 3 cm  1.5 cm size. With loading masses above 6 mg the lm loses its stability in water, conrming optimal lm formation at 6 mg for 3 cm  1.5 cm.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, few research groups including ourselves have reported that electrochemical surface reconstruction due to etching of a constituent from an electrocatalyst often turns out to be beneficial for electrocatalytic activity . The etching process exposes a higher number of catalytic centers that otherwise lay inactive due to their position in the bulk, to the electrolyte . In this article, a similar trend was observed; i.e., with increased vanadate etching, the activity steadily increased.…”
mentioning
confidence: 98%
“…21 The etching process exposes a higher number of catalytic centers that otherwise lay inactive due to their position in the bulk, to the electrolyte. 22 In this article, a similar trend was observed; i.e., with increased vanadate etching, the activity steadily increased. We believe that, due to the polymeric structure of metavanadate, its etching from the material would tear off a long chain of vanadate thereby aiding the transformation of the material to its active phase.…”
mentioning
confidence: 99%
“…4b, the even distribution of the elements only including carbon, oxygen and cobalt elements, suggests that the Co spin-orbit peaks, respectively. 26,27 Two shakeup satellite (labeled as "Sat.") peaks (at 790.2 and 805.1 eV) can also be observed in the XPS spectra of the Co 3 O 4 @LIG nanocomposite, which is in good agreement with the previous reports.…”
Section: Papermentioning
confidence: 99%